Reductively PEGylated carbon nanomaterials and their use to nucleate 3D protein crystals: a comparison of dimensionality - Leese, Hannah S. (Royal Society of Chemistry, 2016)

(untitled) (Chem Sci)
A range of carbon nanomaterials, with varying dimensionality, were dispersed by a non-damaging and versatile chemical reduction route, and subsequently grafted by reaction with methoxy polyethylene glycol (mPEG) monobromides. The use of carbon nanomaterials with different geometries provides both a systematic comparison of surface modification chemistry and the opportunity to study factors affecting specific applications. Multi-walled carbon nanotubes, single-walled carbon nanotubes, graphite nanoplatelets, exfoliated few layer graphite and carbon black were functionalized with mPEG-Br, yielding grafting ratios relative to the nanocarbon framework between ca. 7 and 135 wt%; the products were characterised by Raman spectroscopy, TGA-MS, and electron microscopy. The functionalized materials were tested as nucleants by subjecting them to rigorous protein crystallization studies. Sparsely functionalized flat sheet geometries proved exceptionally effective at inducing crystallization of six proteins. This new class of nucleant, based on PEG grafted graphene-related materials, can be widely applied to promote the growth of 3D crystals suitable for X-ray crystallography. The association of the protein ferritin with functionalized exfoliated few layer graphite was directly visualized by transmission electron microscopy, illustrating the formation of ordered clusters of protein molecules critical to successful nucleation.